2020
DOI: 10.1101/2020.06.12.20129825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

National Smoking Rates Correlate Inversely with COVID-19 Mortality

Abstract: IntroductionRecent studies show cigarette smokers are markedly under-represented among patients hospitalized for COVID-19 in over a dozen countries. It is unclear if this may be related to confounding factors such as age distribution, access to care, and inaccurate records. We hypothesized that these concerns could be avoided by studying smoking prevalence in relation to COVID-19 mortality. Since climate has been identified as a factor in COVID-19, we studied groups of countries with relatively comparable temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…The former is more likely as a large study (114,545 individuals) in Israel recently showed that the risk of SARS-CoV-2 positive testing in smoking individuals is reduced by half 26 . Similarly, Norden et al reported an inverse association between national smoking rates and COVID-19 mortality 27 and this was confirmed in a meta-analysis showing an unexpectedly low prevalence of current smoking among patients with COVID-19 in China 28 . When analyzing the concentrations of IgG in plasma, we found no differences between males and females, nor in smoking habits.…”
Section: Discussionmentioning
confidence: 76%
“…The former is more likely as a large study (114,545 individuals) in Israel recently showed that the risk of SARS-CoV-2 positive testing in smoking individuals is reduced by half 26 . Similarly, Norden et al reported an inverse association between national smoking rates and COVID-19 mortality 27 and this was confirmed in a meta-analysis showing an unexpectedly low prevalence of current smoking among patients with COVID-19 in China 28 . When analyzing the concentrations of IgG in plasma, we found no differences between males and females, nor in smoking habits.…”
Section: Discussionmentioning
confidence: 76%
“…The study also reported that for each percentage point increase in the smoking rate, mortality decreased by 0.147 per 100,000 population 15 . The review of 174 studies described there is uncertainty about the relationship between smoking and COVID-19 and decreased risk of COVID-19 infection among current smokers 15 .…”
Section: Bodymentioning
confidence: 88%
“…A recent US study revealed that there is an inverse relationship between current daily smoking prevalence and COVID-19 for both hot (-0.78, P=0.0002) and cold countries (R=-0.57, P=0.0046) 15 . The study also reported that for each percentage point increase in the smoking rate, mortality decreased by 0.147 per 100,000 population 15 .…”
Section: Bodymentioning
confidence: 98%
See 1 more Smart Citation
“…Norden et al [107] were also interested in studying smoking prevalence and its relation to COVID-19 mortality. They have analysed groups of patients belonging to a few countries/cities with comparable temperatures (from hottest and coldest countries, to avoid the influence of climate), and later correlated their results with the national smoking rate, sex ratio, obesity, temperature and elderly individuals.…”
Section: Medical Conditions -Comorbidities and Associated Inflammationmentioning
confidence: 99%